Effect of structural properties of organosolv lignins isolated from different rice husks on their liquefaction using acidic ionic liquids - Singh, Sandip K.; Dhepe, Paresh L. (Clean Technologies and Environmental Policy, 2018)
Lignin is the only naturally available sustainable resource of aromatic compound on the Earth. Depending on the properties of lignin and the reaction conditions employed for the liquefaction, it is observed that the product distribution alters. Since ionic liquids (ILs) are considered as green and have tuneable properties, in the current work, imidazolium-based acidic ILs were employed to liquefy organosolv lignins derived from different varieties of rice husks. When liquefaction was carried out at 120 A degrees C for 1 h 36% yield for EtOAc- and DEE-soluble products with high mass balance (97 +/- 3%) was observed. The detailed characterisations of lignins and organic solvent-soluble products were done by variety of techniques [GC-MS, FT-IR, UV-Vis, 2D (HSQC) NMR], and based on this, the correlation between activity and properties of catalyst and lignin was established. Depolymerisation of organosolv lignin (derived from three rice husks) into aromatic product was done, and experimental correlation studies were performed in both.

Experimental evidences for existence of varying moieties and functional groups in assorted crop waste derived organosolv lignins - Singh, Sandip K.; Dhepe, Paresh L. (Industrial Crops and Products, 2018)
Isolation of organosolv lignins (ORGLs, water:ethanol, 180 degrees C, 1 h, 93 +/- 5% mass balance) from various lignocellulosic materials like rice husk (RH), wheat straw (WS), bagasse (BG) & wood chips (WC) was done and experimental evidences are provided to perceive the differences in the structures of isolated lignins. To achieve this on bulk level, lignins were characterized by XRD, GPC, TGA & elemental analysis and on molecular level using UV-vis, ATR, 1D/2D HSQC NMR techniques. Besides isolated lignins, crop wastes and pulps were also characterized to divulge details on their properties. It was revealed that lignins have varying concentrations of sinapyl (S), coniferyl (G) and p-coumaryl alcohols (H) and tricin (T) moieties. While, Tricin (T) type lignin moieties are observed only in RH and WS derived lignins, RH derived lignin has higher concentration of side chains than other isolated lignins. Additionally, it is discovered that most lignins have G as main moiety.